2010
DOI: 10.1104/pp.109.149823
|View full text |Cite
|
Sign up to set email alerts
|

Polyphosphoinositides Are Enriched in Plant Membrane Rafts and Form Microdomains in the Plasma Membrane

Abstract: In this article, we analyzed the lipid composition of detergent-insoluble membranes (DIMs) purified from tobacco (Nicotiana tabacum) plasma membrane (PM), focusing on polyphosphoinositides, lipids known to be involved in various signal transduction events. Polyphosphoinositides were enriched in DIMs compared with whole PM, whereas all structural phospholipids were largely depleted from this fraction. Fatty acid composition analyses suggest that enrichment of polyphosphoinositides in DIMs is accompanied by thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 77 publications
5
85
0
Order By: Relevance
“…Moreover, immunoelectron microscopy experiments have revealed that lateral segregation of lipids and proteins occurs at the nanoscale level at the tobacco PM, thus correlating detergent insolubility with membrane domain localization of presumptive raft proteins (Raffaele et al, 2009;Furt et al, 2010;Demir et al, 2013). Together, these data point to the existence of specialized lipid domains in plants.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Moreover, immunoelectron microscopy experiments have revealed that lateral segregation of lipids and proteins occurs at the nanoscale level at the tobacco PM, thus correlating detergent insolubility with membrane domain localization of presumptive raft proteins (Raffaele et al, 2009;Furt et al, 2010;Demir et al, 2013). Together, these data point to the existence of specialized lipid domains in plants.…”
mentioning
confidence: 69%
“…Multidistance spatial cluster statistics analysis (Ripley's k function) of the immunogold-labeled ganglioside GM1 showed spatial aggregation in normal mouse fibroblasts for distances ranging from 32 to 68 nm (Fujita et al, 2007). Similarly, plant-based immunoelectron microscopy experiments have revealed partitioning of both the lipid phosphatidylinositol 4,5-bisphosphate into 25-nm clusters on the PM of tobacco BY2 cells (Furt et al, 2010) and the protein flotillin into clusters of less than 100 nm on the PM of Arabidopsis roots apices (Li et al, 2012). In addition, the protein remorin was observed by immunoelectron microscopy in domains of about 80 nm in the cytosolic leaflet of the membrane of tobacco leaves (Raffaele et al, 2009) and was more recently localized by stimulated emission depletion microscopy within domains of 97 nm in Arabidopsis, whereas the apparent size of these domains was about 250 nm, using classical confocal microscopy (Demir et al, 2013).…”
Section: Cryptogein Induces a Spatial Rearrangement Of The Pm Order Lmentioning
confidence: 93%
“…of lipids bound in vitro. Interestingly, these lipids are enriched in membrane rafts from plants (Vermeer et al, 2009;Furt et al, 2010) or animal cells (Hope and Pike, 1996;Pike et al, 2002), suggesting that RemCA lipidspecificity contributes to driving the segregation of StREM1.3 into membrane microdomains.…”
Section: Remca Directly Binds To Lipid Bilayers In Vitromentioning
confidence: 99%
“…Indeed, polyphosphoinositides and sphingolipids are enriched in membrane rafts from plants (Vermeer et al, 2009;Furt et al, 2010) and animal cells (Hope and Pike, 1996), the latter being also enriched in phosphatidylserine (PS) (Pike et al, 2002). The ability to specifically target DIMs, therefore, might be related to the differential affinity of RemCA to certain negative lipids, as known for SNARE proteins (Mima and Wickner, 2009).…”
Section: Toward Understanding the Molecular Bases Of Specific Associamentioning
confidence: 99%
See 1 more Smart Citation